Abu Hamid Al-Ghazali's Perspective on Authority and Religion - Ihsan, Nur Hadi; Rokhman, Iwan Aminur; Heryanto, Heryanto (University of Darussalam Gontor, Indonesia, 2024)
This article explores the concept of authority and its relationship with religion, addressing various aspects and theories related to both. This concept is significant as it touches on essential elements of society. In faciliting the research process, the researcher employs a descriptive and analytical method with a philosophical basis. As a result, the study finds a connection between authority in al-Ghazali's view and other concepts, such as justice, which ultimately leads to happiness. Authority is necessary in social life as a means to achieve happiness for both individuals and society. This reflects what can be described as the ideal society concept in al-Ghazali's perspective. Al-GhazÄlÄ« proposes that an ideal society is a blend of worldly reality and spirituality, where power must be exercised according to religious teachings by leaders who embody magnanimity, in order to achieve happiness and justice within the community.